(untitled) (Global Journal of Management and Business Research, 2018)
Business failures has been blamed on the inability of the financial manager to plan and control the working capital of their respective firms. These reported inadequacies among financial managers is still evident today in eneo Cameroun in the form of high bad debts, high inventory cost etc. This study is out to examine the effect of working capital management on the profitability of limited liabilities companies in Cameroon the case of eneo. Using secondary data from 2010 to 2017 and with the help of Ordinary Least Square technique, we observed that ICP, AAR and AAP exerts a negative significant influence on the profitability of eneo Cameroon S.A. As a result of this we recommended that the Inventory Convention Period of eneo Cameroon S.A should be reduce by having an Economic Order Quantity of all the stocks in the warehouse and that eneo Cameroon S.A should implement policies that will entice their customers to pay faster such as allowing discount to customers who pay their dues promptly or within the due date.